Optimization and Validation of LLE-LTP and QuEChERS Methodologies for Determining 2,4-D in Water Samples - Freitas,Lucas V. P. (2020)
2,4-Dichlorophenoxyacetic acid (2,4-D) has been one of the main herbicides used to control weeds, however, due to its high use it can promote episodes of environmental contamination. Therefore, this study aimed to optimize and validate the liquid-liquid extraction with low-temperature partition (LLE-LTP) and the quick, easy, cheap, effective, rugged, and safe (QuEChERS) methods for determining 2,4-D in water samples by high performance liquid chromatography with diode array detector. The recovery percentages of the two methodologies were close to 100 ± 3%, and the limits of quantification were 2.0 and 3.1 µg L-1 for LLE-LTP and QuEChERS, respectively. The methodologies were selective and presented linearity from 2.0-26.0 and 3.1-40.6 µg L-1 for LLE-LTP and QuEChERS, respectively. The LLE-LTP was better than QuEChERS due to a smaller number of steps, lower reagent consumption, higher concentration factor and a lower limit of quantification. The real samples did not reveal any environmental contamination episodes by 2,4-D.